Konteks dan Asumsi dalam Perumusan Model Ekonometrika Kebijakan Ekonomi - Muhamad Dafian Abidin; Muhammad Zaini; Imrona Hayati (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This article examines the role of context and underlying assumptions in the formulation of econometric models for economic policy analysis. While econometric models are widely employed to support policy decisions, their construction is often treated as a purely technical process, overlooking the contextual factors that shape variable selection, model specification, and interpretation of results. This study explores how institutional settings, policy objectives, and behavioral considerations influence the assumptions embedded in econometric modeling. By drawing on policy documents, academic literature, and illustrative cases from applied economic research, the article highlights how implicit assumptions may affect the validity and relevance of econometric outcomes. The analysis emphasizes that econometric models are not value-neutral tools but are shaped by theoretical choices and contextual judgments made during their formulation. Understanding these dimensions is crucial to avoid misinterpretation of empirical findings and to enhance the usefulness of econometric analysis in policymaking. The study contributes to the methodological discussion in applied econometrics by encouraging greater transparency and reflexivity in model construction, particularly in the context of economic policy evaluation.